MEMORY STIMULATION, INTERVENTION INCREASE ELDERLY COGNITIVE FUNCTION - Kushariyadi Kushariyadi (Universitas Airlangga, 2017)
Introduction: Physiologically elderly experience irreversible decline in cognitive function due to the aging process and progressive degenerative changes. Memory care promotion can be used in adolescents and adults, however, its use in elderly still need explanation. The research was aimed to improve the memory of elderly using memory care promotion. Method: Type of research was quasy-experimental, two group pre-post treatment design. Sample size were 30 respondents. taken using simple random sampling technique. The research took place in nursing homes Mojopahit Mojokerto in April 2013. The instruments used were memory care promotion module and cognitive function questionairre. Wilcoxon signed rank test and mann whitney test were used to analyze the data with a significance level of α < 0.05. Result: The result showed there were differences in orientation levels (p <0.003), no difference in registration levels (p < 1.000), differences in attention and calculation levels (p < 0.039) differences in recall levels (p < 0.046), differences in language levels (p < 0.035), differences in the cognitive function (p < 0.001), and differences in the cognitive function between treatment group and the control group (p < 0.002). Discussion: Memory care promotion using the theory of therapeutic nurse-patient relationship and functional consequences theory can significantly improve elderly memory. The use of memory care promotion needs the cooperation and active participation of all parties.